Study of The Protection of Children from Sexual Offences Act (POCSO Act) and it provisions - Sharma, Akanksha; Kumar, Dr sunil (Innovative Research Thoughts, 2017)
POCSO or The Protection of Children from Sexual Offences Act (POCSO Act) 2012 was established to protect the children against offences like sexual abuse, sexual harassment and pornography. It was formed to provide a child-friendly system for trial underneath which the perpetrators could be punished. The Act defines a child as any person below eighteen years of age. It also makes provisions for avoiding the re-victimization of the child at the hands of the judicial system. Protection of Children from Sexual Offences Act, 2012 received the President’s assent on June 19, 2012. It was notified in the Gazette of India on June 20, in the same year.